Exploring the public's experience field perception of AR filter media characteristics under CMC - Di, Zhang; Alsagoff, Syed Agil; Yasin, Megat Al Imran; Mohammad Razi, Siti Aishah (International Academic Research, 2022)
Sharing selfies has become a popular habit on social media. Traditional beauty filters only complete functions such as whitening and face-lifting on the basis of taking pictures. However, with AR technology entering the realm of mobile photography filters, computer graphics (CG) are superimposed on selfies, allowing senders to manage their impressions more virtually and freely. This paper explores the influence of media attributes of AR selfie filters under Computer-Mediated Communication (CMC) from the perspective of media ecology theory. Explore this phenomenon through a qualitative phenomenological approach. Use in-depth interviews and focus groups to collect data. This paper discusses the impact of AR selfie, a new media, in CMC, and expands the application scope of media ecology theory in CMC emerging media. It also provides a basic understanding for the further communication impact of AR selfie on the sender and receiver in CMC. This can provide basic policies and related references for the government to formulate media policies and social media management regulations, and can also be used as literature for other scholars to refer.